1993
DOI: 10.1210/jcem.77.5.8077313
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxytocin on free intracellular Ca2+ levels and progesterone release by human granulosa-lutein cells.

Abstract: Oxytocin and its receptor are found in the corpus luteum in a variety of species, including the human.In the present study we used fura- T HE SYNTHESIS of oxytocin in the corpus luteum of the ovary is well established and occurs in a variety of species (l-3; for review, see Ref. 4), including the human (5-8). Moreover, indirect evidence for the presence of oxytocin receptors in human granulosa-lutein cells was provided by a study that showed inhibitory effects of oxytocin on FSHstimulated estradiol secretion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It was hypothesized to act locally, e.g., as a luteolytic factor (3133), because local production was accompanied by expression of the OT receptor (OTR) (3436). Two studies in human mural GCs built on these results (37, 38) and confirmed expression of the receptor in GCs and CL. Exogenously applied to human GCs, OT acutely within seconds elevated the levels of intracellular Ca 2+ and within hours, changed progesterone production (37).…”
Section: A Sodium Channel Oxytocin Pedf and Decorin Are Involved Imentioning
confidence: 71%
See 1 more Smart Citation
“…It was hypothesized to act locally, e.g., as a luteolytic factor (3133), because local production was accompanied by expression of the OT receptor (OTR) (3436). Two studies in human mural GCs built on these results (37, 38) and confirmed expression of the receptor in GCs and CL. Exogenously applied to human GCs, OT acutely within seconds elevated the levels of intracellular Ca 2+ and within hours, changed progesterone production (37).…”
Section: A Sodium Channel Oxytocin Pedf and Decorin Are Involved Imentioning
confidence: 71%
“…Two studies in human mural GCs built on these results (37, 38) and confirmed expression of the receptor in GCs and CL. Exogenously applied to human GCs, OT acutely within seconds elevated the levels of intracellular Ca 2+ and within hours, changed progesterone production (37). A further downstream role of OT in the induction of apoptosis of GCs became apparent in a follow-up study, also employing IVF-derived GCs.…”
Section: A Sodium Channel Oxytocin Pedf and Decorin Are Involved Imentioning
confidence: 71%
“…The stimulation protocols (i.e. the “long” protocol), were described 9,10,4144 . The ethics committee of the Ludwig-Maximilians University Munich approved the use of follicular aspirates and GCs for scientific experiments (Project 323-05).…”
Section: Methodsmentioning
confidence: 99%
“…The K Ca channels play a role in producing sex steroid hormones that are induced by gonadotropins (Kim et al, 2020). The involvement of BK channels in intracellular calcium signaling and progesterone release in luteinizing GCs emphasizes the importance of these channels in the control of female reproductive hormones (Mayerhofer et al, 1993).…”
Section: Bk Channel In the Reproductive Systemmentioning
confidence: 99%